Clinical characteristics and survival outcomes of patients with pneumonectomies: A population-based study - Linlin Wang; Lihui Ge; Guofeng Zhang; Ziyi Wang; Yongyu Liu; Yi Ren (Frontiers in Surgery, 2022)
BackgroundPrognostic factors in a pneumonectomy (PN) are not yet fully defined. This study sought to analyze and evaluate long-term survival after pneumonectomies (PNs) for patients with non-small cell lung cancer (NSCLC).MethodsWe obtained data from the Surveillance, Epidemiology, and End Results (SEER) database for patients who underwent PNs between 2004 and 2015. Propensity score matching (PSM) analysis and Kaplan–Meier curves were used to estimate overall survival (OS), while univariate and multivariable Cox proportional hazards regression analyses were applied to create a forest plot.ResultsIn total, 1,376 patients were grouped according to right/left PNs. Before matching, OS was worse after a right PN [hazard ratio (HR): 1.459; 95% CI 1.254–1.697; P < 0.001] and after matching, survival differences between groups were not significant (HR: 1.060; 95% CI 0.906–1.240; P = 0.465). Regression analysis revealed that age, gender, grade, lymph node dissection, N-stage, and chemotherapy were independent predictors of OS (P < 0.05). Chemotherapy was associated with improved OS (P < 0.001).ConclusionsLaterality was not a significant prognostic factor for long-term survival after a PN for NSCLC. Chemotherapy was a significant independent predictor of improved OS. Long-term survival and outcomes analyses should be conducted on larger numbers of patients.